2020
DOI: 10.3390/antiox9060483
|View full text |Cite
|
Sign up to set email alerts
|

A Mixture of Algae and Extra Virgin Olive Oils Attenuates the Cardiometabolic Alterations Associated with Aging in Male Wistar Rats

Abstract: Aging is one of the major risk factors for suffering cardiovascular and metabolic diseases. Due to the increase in life expectancy, there is a strong interest in the search for anti-aging strategies to treat and prevent these aging-induced disorders. Both omega 3 polyunsaturated fatty acids (ω-3 PUFA) and extra virgin olive oil (EVOO) exert numerous metabolic and cardiovascular benefits in the elderly. In addition, EVOO constitutes an interesting ingredient to stabilize ω-3 PUFA and decrease their oxidation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 83 publications
(89 reference statements)
6
24
0
Order By: Relevance
“…This could be the reason why the old animals treated with the oil mixture had the same inflammatory profile in serum [31] and in skeletal muscle as the young ones, as can be seen in the present study. This oil mixture also had anti-oxidant effects [31]; its administration to the same cohort of animals reduced the oxidative status in the liver, heart, and vasculature. Increased emission of reactive oxygen species (ROS) has proven to be involved in sarcopenia [38], which is another way that the oil treatment can reduce the harmful effects of these molecules.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This could be the reason why the old animals treated with the oil mixture had the same inflammatory profile in serum [31] and in skeletal muscle as the young ones, as can be seen in the present study. This oil mixture also had anti-oxidant effects [31]; its administration to the same cohort of animals reduced the oxidative status in the liver, heart, and vasculature. Increased emission of reactive oxygen species (ROS) has proven to be involved in sarcopenia [38], which is another way that the oil treatment can reduce the harmful effects of these molecules.…”
Section: Discussionsupporting
confidence: 82%
“…[34]. We have previously described the higher profile of inflammatory cytokines and oxidative parameters in the same cohort of old animals [31]. In the present study, we observed that skeletal muscle in old rats had an increased level of pro-inflammatory cytokine IL-6 and a decreased level of anti-inflammatory cytokine IL-10.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Besides, several ‘anti-aging’ nutraceutical compounds have been recently proposed to counteract oxidative stress and senescence [ 40 ]. For example, both omega 3 polyunsaturated fatty acids (ω-3 PUFA) and extra virgin olive oil (EVOO) have been reported to exert numerous metabolic and cardiovascular benefits in the elderly due to their high content in antioxidant compounds [ 199 , 200 , 201 , 202 ]. In old rats, the treatment prevented aging-induced endothelial dysfunction, oxidative stress, inflammation, and vascular insulin resistance through activation of the PI3K/Akt pathway and decreasing the response to the vasoconstrictor angiotensin II [ 202 ].…”
Section: New Therapeutic Approaches Targeted Endothelial Dysfunctimentioning
confidence: 99%
“…For example, both omega 3 polyunsaturated fatty acids (ω-3 PUFA) and extra virgin olive oil (EVOO) have been reported to exert numerous metabolic and cardiovascular benefits in the elderly due to their high content in antioxidant compounds [ 199 , 200 , 201 , 202 ]. In old rats, the treatment prevented aging-induced endothelial dysfunction, oxidative stress, inflammation, and vascular insulin resistance through activation of the PI3K/Akt pathway and decreasing the response to the vasoconstrictor angiotensin II [ 202 ]. Moreover, the Citrus flavonoid naringenin (NAR) has been demonstrated to exert anti-senescence effects, and, when administered to old mice, it reduced ROS production in myocardial tissue, inflammation, and vascular remodeling [ 203 ].…”
Section: New Therapeutic Approaches Targeted Endothelial Dysfunctimentioning
confidence: 99%